Combined Plaque Incision, Buccal Mucosa Grafting, and Additional Tunica Albuginea Plication for Peyronie's Disease. Issue 1 (11th December 2018) - Cormio, Luigi; Mancini, Vito; Massenio, Paolo; d'Altilia, Nicola; Selvaggio, Oscar; Di Fino, Giuseppe; Selvaggi, Gennaro; Carrieri, Giuseppe
Abstract: Introduction: Surgery remains the gold standard for treatment in stable patients with penile deformity associated to Peyronie's disease (PD). Aim: To evaluate the long-term results of plaque incision and buccal mucosa grafting (BMG), with or without additional tunica albuginea plication (TAP), in the correction of severe penile curvatures secondary to PD. Methods: 72 patients with severe curvature caused by PD, normal erections, and stable disease entered this prospective study. Preoperatively, they underwent penile duplex ultrasounds with measurement of curvature and length of affected side. All procedures were carried out by 1 surgeon. Patients were seen at 1, 3, 6, and 12 months postoperatively, then yearly. Subjective outcome was assessed by the Sexual Encounter Profile (SEP) questionnaire, and objective outcome was assessed by an intracavernous injection (ICI) test performed within the first year for evaluating penile rigidity, straightness, and length. Main Outcome Measure: Long-term outcomes include penile straightening, penile shortening, and sexual satisfaction. Results: Mean curvature was 71.32 ± 17.6° (range 40–110); 33 (45.8%) patients had a 2-sided curvature with a mean second curvature of 33.79 ± 12.2° (range 10–60). Additional TAP was needed in 60% of patients for complete straightening or graft stretching. All patients resumed unassisted intercourse 1 month after surgery; 4 (5.5%) refused follow-up, claiming excessive penile shortening. In the remaining 68, the ICI test showed no recurvature, shortening, or de novo erectile dysfunction. At mean follow-up of 62.01 ± 34.3 months (range 12–135), all were able to obtain an erection (SEP-1), 97.1% to penetrate (SEP-2), and 89.7% to successfully complete intercourse (SEP-3); 80.9% of them were satisfied with erection hardness (SEP-4) and 86.8% were overall satisfied (SEP-5), with the main reason for dissatisfaction being expectation of better length and rigidity. Conclusion: BMG, with or without TAP, provides excellent long-term results and is safe and reproducible, representing a valuable treatment option for PD, but great care should be taken in patient counseling to avoid unrealistic expectations.